Sadko opera in seven scenes - Rimskij-Korsakov, Nikolaj 1844-1908 (BelAir Classiques, 2021)
In the thirteenth century, the rich merchants of Novgorod mock the dreams of far-away journeys and commercial conquests brought forth by Sadko, a musician, and singer. But Volkhova, the Sea King's daughter, is enchanted by Sadko's voice and promises to help him fulfill his dreams... Sadko is a decisive work in Nikolai Rimsky-Korsakov's aesthetic evolution. As in many operas, the composer draws his artistic material from Russian folk and fairytales, but also old musical and poetic forms. The result is a prodigious opera, whose modernity both dramatic and musical erupts from the fabulous resources of traditional Russian epics, but also the wonders of the marine universe, close to his former navigator self's heart. A subtle analyst of the Slavic soul, stage director Dmitri Tcherniakov comes back to the great stage of the Bolshoi Theater and devises a surprising production that perfectly underlines the ambiguities of this paradoxical opera, between past and present, fantasy and reality
Interpreten unter anderem: Nazhmiddin Mavlyanov (Sadko). Aida Garifullina (Volkhova). Ekaterina Semenchuk (Lubava Buslaevna). Yuri Minenko (Nezhata). Bolshoi Theatre of Russia Orchestra and Chorus. Timur Zangiev (Dirigent)
Aufnahme: Moskau, Bolshoi Theater, Januar 2020
Bildformat: 16:9
Keywords: Operas; Feature films; Film; Blu-Ray-Disc